2021
DOI: 10.1111/acer.14653
|View full text |Cite
|
Sign up to set email alerts
|

Gender moderates the association between acute alcohol intoxication and facial emotion recognition in a naturalistic field study setting

Abstract: BackgroundAlcohol intoxication is associated with significant negative social consequences. Social information processing theory provides a framework for understanding how the accurate decoding and interpretation of social cues are critical for effective social responding. Acute intoxication has the potential to disrupt facial emotion recognition. If alcohol impairs the processing and interpretation of emotional cues, then the resultant behavioral responses may be less effective. The current study tested the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Alcohol and other intoxicants have significant effects on the psychomotor system, altering cognitive abilities and perception. Fear and threat awareness are dampened, the sensation of pain decreases (Hoaken & Stewart, 2003 ), the responsiveness to nonverbal cues reduces (Attwood & Munafò, 2014 ; Melkonian & Ham, 2016 ), and the willingness to engage in risky behavior increases (Miller & Fillmore, 2014 ). Several studies have demonstrated that blood alcohol levels above a certain concentration can facilitate aggression (Chermack & Giancola, 1997 ; De Sousa Fernandes Perna et al, 2016 ; Duke et al, 2011 ; Giancola, 2002 ; Kuypers et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol and other intoxicants have significant effects on the psychomotor system, altering cognitive abilities and perception. Fear and threat awareness are dampened, the sensation of pain decreases (Hoaken & Stewart, 2003 ), the responsiveness to nonverbal cues reduces (Attwood & Munafò, 2014 ; Melkonian & Ham, 2016 ), and the willingness to engage in risky behavior increases (Miller & Fillmore, 2014 ). Several studies have demonstrated that blood alcohol levels above a certain concentration can facilitate aggression (Chermack & Giancola, 1997 ; De Sousa Fernandes Perna et al, 2016 ; Duke et al, 2011 ; Giancola, 2002 ; Kuypers et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%